Economic survey of Latin America and the Caribbean 1984 - United Nations (Santiago, Chile : United Nations, 1986)
The Economic Survey of Latin America and the Caribbean is issued annually by the Economic Development Division of the Economic Commission for Latin America and the Caribbean (ECLAC). It covers the economic situation in Latin America and the Caribbean and provides a concurrent economic overview of the region, as provided by the Division and other experts based on statistical indicators which are collected annually.
"LC/G."
Issued in parts, 1982-1985, 1986, 1990-1993.
Some vols. have also a distinctive title.
rpm 27/11/2017
Loans
Keywords: Economic history; Latin America; Caribbean Area; Caribbean Area; Latin America